Irradiation effect on impact fracture behavior of A508-3 steel in ductile-to-brittle transition range. (March 2019) - Zhou, Ziyang; Tong, Zhenfeng; Qian, Guian; Zhong, Weihua; Wang, Chenglong; Yang, Wen; Berto, Filippo
Abstract: The mechanical performance of reactor pressure vessel (RPV) materials is an important factor in determining the safety and economics of the operation of a nuclear power plant. The ductile-to-brittle transition temperature (DBTT) tested by Charpy impact test is an important parameter for evaluating the RPV embrittlement. In this paper, the Charpy impact test of RPV steel prior and after irradiation was carried out at different temperatures. The fracture morphology was observed by scanning electron microscopy. The irradiation effect on the impact fracture behavior was analyzed in the DBTT temperature zone. Results show that in the DBTT range, the crack initiation and propagation energy are obviously reduced for the irradiated material. After irradiation, the dimple area on the fracture surface is significantly reduced, and the distance from the crack initiation source to the gap is decreased. For the RPV steel with low Cu steel content, matrix damage becomes the main factor on material irradiation embrittlement. Highlights: USE decreases by 61J, and the DBTT increases by 68 °C due to irradiation embrittlement. Decrease of crack propagation energy is the main reason for toughness reduction. Irradiation leads to the reduction of dimple area and plastic deformation. Distance from the crack initiator to the notch root is significantly reduced.